2016
DOI: 10.18632/oncotarget.13163
|View full text |Cite
|
Sign up to set email alerts
|

The associations between mast cell infiltration, clinical features and molecular types of invasive breast cancer

Abstract: Associations between mast cell infiltration and the clinical features and known molecular profile of breast cancer remain unclear. The distribution difference of mast cell was evaluated, in 219 patients with no special type of invasive carcinoma, using sorts of age, max diameter of cancer, histological type, lymph node metastasis as well as the expressions of estrogen receptor (ER), progestogen receptor (PR), human epidermal growth factor receptor 2 (HER-2) and nuclear protein Ki67. The mast cell density (MCD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
2
19
2
Order By: Relevance
“…tumorigenic molecules (e.g., TNF-α and IL-90), thus, their role on breast cancer is controversial (5). Some scholars believe that mast cell infiltration suggests a good prognosis of breast cancer: similar to our results, three other groups have observed high MCs density in luminal A and B types of breast cancer, which can be hormonally treated and have a better prognosis (6,10,17). This suggests that MCs are associated with less aggressive tumors.…”
Section: Cells (Mcs) In Breast Carcinomas Stained For Anti-tryptase (supporting
confidence: 65%
See 2 more Smart Citations
“…tumorigenic molecules (e.g., TNF-α and IL-90), thus, their role on breast cancer is controversial (5). Some scholars believe that mast cell infiltration suggests a good prognosis of breast cancer: similar to our results, three other groups have observed high MCs density in luminal A and B types of breast cancer, which can be hormonally treated and have a better prognosis (6,10,17). This suggests that MCs are associated with less aggressive tumors.…”
Section: Cells (Mcs) In Breast Carcinomas Stained For Anti-tryptase (supporting
confidence: 65%
“…Some groups have concluded that the prognosis is worse with a higher density of mast cells in the breast cancer tissue (10). Xiang et al have observed more numerous peritumoral MCs in G3 breast cancers, increased tryptase being associated with higher tumor grade and more lymph node metastasis compared to lower grades.…”
Section: Cells (Mcs) In Breast Carcinomas Stained For Anti-tryptase (mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the percentage of Ki67 expression is closely related to the degree of differentiation, invasion, metastasis and prognosis of many tumors . As shown in Figure c , Ki67 immunostaining showed less proliferation in xenograft tumors of lncXLEC1‐ upregulated cells than in controls.…”
Section: Resultsmentioning
confidence: 71%
“…It has been reported that the percentage of Ki67 expression is closely related to the degree of differentiation, invasion, metastasis and prognosis of many tumors. 22 As shown in Figure 4c, Ki67 immunostaining showed less proliferation in xenograft tumors of lncXLEC1-upregulated cells than in controls. We categorized the endometrial tissues according to the percentage of Ki67 expression (>30%, strong staining and <30%, weak staining) and analyzed the expression of lnc-XLEC1 in 30 EC tissues.…”
Section: Effects Of Lnc-xlec1 On Tumor Growthmentioning
confidence: 71%